Subsidies and Countervailing Measures: Challenges in International Trade Law - Supriyo, Agus; Wicaksana Prakasa, Satria Unggul (Jurnal Komunikasi Hukum, 2021)
In the global era with all demands and expectations for a better economic condition in a country that an international trade is needed. Fair competition can be carried out in competition between business actors and commodity (goods or services) in overseas with business actors and commodity (goods or services) in country. One form of creating justice in international trade competition is by providing subsidies. The issue of subsidies created the problems and disputes. The problem formulations of this research were: (1) how are the effects of subsidies and countervailing in international trade regulations? (2) how is the case analysis related to subsidies and countervailing measures according to the provisions of the GATT 1994, The SCM Agreement and other legal provisions? The results showed that (1) the effect of subsidies and countervailing measures based on their types (red light, yellow light, green light) in international trade regulations had provided clear provisions as well as the impact and limitations in implementing these provisions in accordance with the provisions. GATT 1994 and The SCM Agreement. (2) The several cases described regarding subsidies that were not allowed because they created injustice that the subsidies were only carried out in an emergency situation and their nature rescued them from an economic crisis.